Hubungan Karakteristik Dan Caring Perawat Dengan Kepuasan Pasien Di Ruang Rawat Jalan Rumah Sakit Siti Aisyah Lubuklinggau Tahun 2025 - Depi Kusmira; Darmawansyah Darmawansyah; Emi Pebriani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Patient satisfaction levels vary from country to country. Satisfaction in developed countries is already high compared to patient satisfaction in developing countries. Satisfaction in developing countries has only reached 80% in terms of healthcare worker service. This figure is still below the minimum service standard set by the government of 90%. The purpose of this study is to determine a correlation between nurses’ characteristics and caring with patient satisfaction in the Outpatient Department of Siti Aisyah Hospital, Lubuklinggau in 2025. The research method used was descriptive research with a cross-sectional approach, using the Chi-Square statistical test. The sampling technique used was purposive sampling with a sample size of 92 patients in the Outpatient Room of Siti Aisyah Hospital, Lubuklinggau. The results of the univariate analysis showed that a small proportion of respondents (20.7%) were male, a small proportion (15.2%) had a basic education, a small proportion (12%) rated the nurses' caring as poor, and a small proportion (19.6%) were dissatisfied. The bivariate analysis results showed that there was a correlation between gender (p-value 0.000), education (p-value 0.000), and caring (p-value 0.000) with patient satisfaction. There was a correlation between characteristics and nursing care with patient satisfaction in the Outpatient Department of Siti Aisyah Hospital, Lubuklinggau in 2025. The researchers recommend that the hospital continue to improve the quality of nursing services through ongoing training, routine monitoring of patient satisfaction, and adjustment of nurses' workloads to optimize interactions with patients.